2017
DOI: 10.1097/ccm.0000000000002380
|View full text |Cite
|
Sign up to set email alerts
|

Activation-Associated Accelerated Apoptosis of Memory B Cells in Critically Ill Patients With Sepsis

Abstract: Depletion of the memory B-cell compartment contributes to the immunosuppression induced by sepsis. Therapies targeted at reversing this immune memory depletion warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 47 publications
(36 reference statements)
4
82
0
Order By: Relevance
“…The roles in sepsis pathology and as a putative biomarker for IVIg therapy warrants further study. (14). High FLC in sepsis could be related to either excess production related to sepsis related inflammation or due to allelic inclusion of light chains in B cells (13,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The roles in sepsis pathology and as a putative biomarker for IVIg therapy warrants further study. (14). High FLC in sepsis could be related to either excess production related to sepsis related inflammation or due to allelic inclusion of light chains in B cells (13,15).…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria included patients <18 years, those with congenital hypogammaglobulinemia, known protein-losing enteropathies, nephrotic syndrome, neoplastic or proliferative hematologic diseases; those having received IVIg therapy in the last 3 months; those receiving high-dose corticosteroid therapy; ongoing blood loss (defined by blood transfusion requirement > 2 units/24 hour period); retroviral disease; and immune dysfunction as defined by Acute Physiology and Chronic Health Evaluation (APACHE) II score co-morbidities (17). We have recently published other details on B cell changes in sepsis from this population, using the same cohort (14).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulatory T cells (Treg), an important T CD4+ T cell subset with immunosuppressive properties, are relatively preserved in sepsis. Total B cell counts are decreased with exaggerated loss of memory B cell subsets despite normal B cell-specific survival factor levels [19], with evidence of B cell exhaustion and increased proportions of regulatory B cells [8]. Preliminary results from an animal model highlight that the antibody-independent effect of B cells on the immune system such as granulocyte-monocyte colony-stimulating factor secretion [16] and cytokine secretion [12] may be relevant in sepsis biology, which require further investigation.…”
Section: Alterations To the Adaptive Immune System In Sepsismentioning
confidence: 99%
“…B-cell apoptosis appears to be greater in memory cells when compared with naive B cells. This suggests that B-cell depletion is not a consequence of impaired bone marrow production 11 . Similarly to the CIGMA investigators and others, we have also found that the combined presence of low levels of the endogenous immunoglobulins IgG1, IgM and IgA in plasma is associated with reduced survival in patients with sepsis and multi-organ failure and the low IgM levels correlated with the high CRP values (courtesy of Dr Heurich-Sevchenko, unpublished data) 4,12 .…”
mentioning
confidence: 95%